Student Response Conceptual Change Text (CCT) As A Media for Learning Energy Concepts in Elementary School Students - Wafa Nur Aisyah; Rahmah Novianti; Agnia Nur Fikriyah; Wati Sukmawati (Postgraduate, University of Mataram, 2023)
This study is a qualitative descriptive study aimed at determining student responses to the use of concept-changed text (CCT)-based materials in science to learn the concept of energy. The data collection technique used was stratified sampling with 114 students in grades IV and V as research subjects. Data were collected using non-testing equipment in the form of questionnaires with Likert scales, distributed after students participated in the learning process, and processed using percentage statistical formulas. The results showed that class IV was 82.13% and class V was 80.63%, both of which were included in the very decent category. Effectively use Conceptual Change Text (CCT) to overcome student misconceptions based on data collection results. In learning using CCT students can independently correct mistakes and difficulties in understanding the concepts they have experienced so far. This research can be a recommendation for other researchers in using CCT-based teaching materials to help students learn.